Treatment Modality for Stage IB Peripheral Non-Small Cell Lung Cancer With Visceral Pleural Invasion and ≤3 cm in Size - Huang, Weijia; Deng, Han-Yu; Lin, Ming-Ying; Xu, Kai; Zhang, Yu-Xiao; Yuan, Chi; Zhou, Qinghua (Frontiers in Oncology, 2022)
Purpose: To compare the survival difference among lobectomy, segmentectomy, and wedge resection, and investigate the role of adjuvant chemotherapy for early-stage small-sized non-small cell lung cancer(NSCLC) with visceral pleural invasion(VPI). Methods: Patients diagnosed with stage IB peripheral NSCLC with VPI and ≤3cm in size in the Surveillance, Epidemiology, and End Results database between 2004 and 2015 were included, and the pleural layer(PL) invasion status was identified to recognize the tumors with VPI, including PL1 and PL2. We conducted Cox proportional hazard model in multivariable analysis, and subgroup analysis via propensity score matching(PSM) method and Cox regression method to figure out the optimal therapy for these patients. Results: A total of 1,993 patients were included, all of which received surgery, and the median follow-up was 33 months(range, 1-83 months). In multivariable analysis, age, gender, histology, pathological grade, lymph nodes examination, surgical approaches, and radiotherapy were independent prognostic factors about OS. Lobectomy was superior to sublobar resection(HR=1.41; 95%CI, 1.08-1.83), and wedge resection was associated with impaired survival compared to lobectomy(HR=1.64; 95%CI, 1.22-2.20) in PSM analyses. In subgroup analysis, lobectomy was superior to sublobar resection among those aged <70 years(HR=1.81; 95%CI, 1.13-2.90), female(HR=1.75; 95%CI, 1.21-2.53), and 1-20mm in size(HR=1.61; 95%CI, 1.11-2.33). No survival benefit was observed for adjuvant chemotherapy. Conclusions: Lobectomy was superior to wedge resection and comparable with segmentectomy for stage IB NSCLC(≤3cm) with VPI, and adjuvant chemotherapy could not benefit these patients, even in those with sublobar resection. The preferred surgical procedure remained to be studied in prospective, controlled trials.